The Off-Label Use of Rituximab for the Management of Inflammatory Disorders: American University of Beirut Medical Center Experience - Dana HARB,; Hiba MOUKADEM,; Rabih NAYFE,; Ali MEHDI,; Abdel Fattah MASRI,; Ziad SALEM,; Ali TAHER,; Imad UTHMAN, (Archives of Rheumatology, 2014)
Objectives: This study aims to evaluate the efficacy of off-label use of rituximab with possible side effects. Patients and methods: Records of the 44 American University of Beirut Medical Center pharmacies were searched for patients who used rituximab over the past 4.5 years, and data on rituximab dosage, protocol and side effects were documented. The majority of patients had systemic lupus erythematosus. Autoimmune thrombocytopenic purpura, antiphospholipid syndrome, Sjögren's syndrome, Wegener’s granulomatosis, autoimmune hemolytic anemia, dermatomyositis, and pemphigus vulgaris were also reported. Outcome measures were improvement in signs and symptoms during a follow-up period of two years. Results: Twenty-nine out of the 44 patients had complete response without relapse. Of those, 12 patients were in remission after the first cycle. Of the systemic lupus erythematosus cases, 12 had complete response without relapse; of which, five patients had remission after the first cycle. No significant toxicities were noted. Conclusion: The off-label use of rituximab in various inflammatory diseases showed improvement in symptoms with no significant side effects in patients who have failed previous treatment with multiple conventional regimens.